2021
DOI: 10.1101/2021.09.24.461616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Broad ultra-potent neutralization of SARS-CoV-2 variants by monoclonal antibodies specific to the tip of RBD

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) continue to wreak havoc across the globe. Higher transmissibility and immunologic resistance of VOCs bring unprecedented challenges to epidemic extinguishment. Here we describe a monoclonal antibody, 2G1, that neutralizes all current VOCs and has surprising tolerance to mutations adjacent to or within its interaction epitope. Cryo-electron microscopy structure showed that 2G1 bound to the tip of receptor binding domain (RBD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…We projected these escape mutations on RBD (Figure 4C) and found that the escape mutations of 5B2 (N370S, N440K, V503M), 9B10 (A475V, E484K), 3A4 (F490L) and 8G9 (N354D, D389N, E484K) were not within the 4 Å distance from ACE2 (Figure 4E) (structure based on PDB ID: 6M17), so these mutations did not affect ACE2-Fc binding and neutralization. But for escape mutation of 2G1 (F486I), although F486I mutation totally lost four π-π stacking interactions with 2G1 (Figure 4F) (structure in our previous study [21]), it also lost one π-π stacking interaction with Y83 of ACE2 (Figure 4G). However, there was still a hydrophobic interaction between I486 of RBD and L79 or M82 of ACE2 (Figure 4G).…”
Section: Ace2-fc Neutralization Against Antibody-escaped Vsv-s Varian...mentioning
confidence: 62%
See 3 more Smart Citations
“…We projected these escape mutations on RBD (Figure 4C) and found that the escape mutations of 5B2 (N370S, N440K, V503M), 9B10 (A475V, E484K), 3A4 (F490L) and 8G9 (N354D, D389N, E484K) were not within the 4 Å distance from ACE2 (Figure 4E) (structure based on PDB ID: 6M17), so these mutations did not affect ACE2-Fc binding and neutralization. But for escape mutation of 2G1 (F486I), although F486I mutation totally lost four π-π stacking interactions with 2G1 (Figure 4F) (structure in our previous study [21]), it also lost one π-π stacking interaction with Y83 of ACE2 (Figure 4G). However, there was still a hydrophobic interaction between I486 of RBD and L79 or M82 of ACE2 (Figure 4G).…”
Section: Ace2-fc Neutralization Against Antibody-escaped Vsv-s Varian...mentioning
confidence: 62%
“…Next, we evaluate the SARS-CoV-2 neutralizing antibodies from convalescent patients developed by our Laboratory 17 to understand whether they might be escaped by Delta or Omicron variants using the pseudovirus assay (Figure 1E). Eleven mAbs interacting with diverse epitopes on the RBD were evaluated (Figure 1F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an B cell antibody repertoire from early stage COVID-19 convalescents 8 , we compared dozens of candidate molecules in neutralizing activity against pseudo-typed SARS-CoV-2 WA1/2020 and Omicron viruses. We found that most of the antibodies that performed well against the WA1/2020 virus nearly lost their neutralization against Omicron; only a few antibodies retained full or partial activity (Fig.…”
Section: Resultsmentioning
confidence: 99%